2007
DOI: 10.1007/s10620-007-9792-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mannan-Binding Lectin Levels in Patients with Celiac Disease: An Analysis of Clinical and Autoimmune Features

Abstract: Mannan-binding lectin (MBL) is the central protein in the activation of complement through the lectin pathway. MBL plasma concentration is genetically determined and varies significantly among individuals. Recent findings suggest that MBL is associated with the pathogenesis of celiac disease (CD). In this study, MBL and C-reactive protein (CRP) levels were determined in 101 celiac patients and 120 controls, with the aim to associate with the presence of gluten in the diet, disease severity, and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…In conclusion, when Biagi and Corazza [33] recently asked if first-degree relatives of CD patients are at an increased risk of developing CD, the experience of the authors [1,3,34,35] and the present results allow us to answer the question affirmatively, especially in relation to the Brazilian population. Undoubtedly, based on its high predictive negative value (100%), only HLA DQ2 and DQ8 typing of serologically negative individuals would make it possible to exclude individuals who are at risk of developing CD in affected families.…”
Section: Discussionsupporting
confidence: 65%
“…In conclusion, when Biagi and Corazza [33] recently asked if first-degree relatives of CD patients are at an increased risk of developing CD, the experience of the authors [1,3,34,35] and the present results allow us to answer the question affirmatively, especially in relation to the Brazilian population. Undoubtedly, based on its high predictive negative value (100%), only HLA DQ2 and DQ8 typing of serologically negative individuals would make it possible to exclude individuals who are at risk of developing CD in affected families.…”
Section: Discussionsupporting
confidence: 65%
“…MBL level exhibits ethnic variation [27]. A difference of approximately 1-3 mg/l on average in mean MBL serum concentrations has been reported from previous studies [27][28][29]. Our results were in complete agreement with these data, as the median levels of MBL were 1·7 mg/ml in healthy controls and 2·3 mg/l in subjects with C1INH deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of substantial difference in CRP levels either implies that systemic inflammation is not important for IHD risk in CD or (more likely) that CRP is not an optimal marker of systemic inflammation in CD. Studies have shown elevated levels of various interleukins and tumour necrosis factor in active CD, but elevated CRP has not been associated with CD in the few published studies on this topic . Another autoimmune disease, systemic lupus erythematosus (SLE), has similarly been linked to an increased risk of atherosclerosis potentially due to chronic inflammation in SLE as these patients lack traditional IHD risk factors .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown elevated levels of various interleukins and tumour necrosis factor 25 in active CD, but elevated CRP has not been associated with CD in the few published studies on this topic. 26,27 Another autoimmune disease, systemic lupus erythematosus (SLE), has similarly been linked to an increased risk of atherosclerosis potentially due to chronic inflammation in SLE as these patients lack traditional IHD risk factors. 28 Assessments of carotid plaques have shown that atherosclerosis is both more common and positively associated with disease duration in both SLE and rheumatoid arthritis.…”
Section: Potential Mechanismsmentioning
confidence: 99%